Development of a novel high granularity crystal electromagnetic calorimeter - Qi Baohua; Guo Fangyi; Liu Yong; Zhao Zhiyu (EPJ Web of Conferences)
The high-granularity crystal calorimeter has been proposed for future lepton colliders with an ex-cellent electromagnetic energy resolution. To evaluate the crystal ECAL performance and validate the design specifications from individual units to the entire detector, extensive R&D activities have been performed. Geometry design along with dedicated software development is currently ongoing. Hardware experiments in both laboratory and beam facilities have been conducted, providing reliable data for the crystal ECAL design.